2021
DOI: 10.3390/ijerph18084339
|View full text |Cite
|
Sign up to set email alerts
|

Dependent, Poorer, and More Care-Demanding? An Analysis of the Relationship between Being Dependent, Household Income, and Formal and Informal Care Use in Spain

Abstract: Population ageing is one of the current challenges that most societies are facing, with great implications for health systems and social services, including long-term care. This increasing long-term care use is particularly rising for dependent older people, motivating the implementation of regional dependency laws to ensure their care needs’ coverage. Using data from the Survey of Health, Ageing, and Retirement in Europe (SHARE) from the year 2004 until 2017, the aim of this study is to assess the impact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Accordingly, our first aim was to determine the institutional care preferences of older people. In recent decades, choices for informal care have led to a low demand for formal care in China, especially for people with functional limitations [12]. On the one hand, evidence has suggested that the family home is not always the best place for eldercare because of scarce supportive resources, the lack of suitable informal caregivers, and the possibility of financial, verbal, and even physical abuse [13].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, our first aim was to determine the institutional care preferences of older people. In recent decades, choices for informal care have led to a low demand for formal care in China, especially for people with functional limitations [12]. On the one hand, evidence has suggested that the family home is not always the best place for eldercare because of scarce supportive resources, the lack of suitable informal caregivers, and the possibility of financial, verbal, and even physical abuse [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we note that the average service hours (per PC or HH) per user vary significantly between CSS zones ( Figure A3 and Figure A4 ). These differences could be related to socioeconomic factors, as pointed out by previous research [ 36 , 38 ].…”
Section: Resultsmentioning
confidence: 80%
“…This study explored which sociodemographic features may influence this phenomenon. Previous research has pointed out features that have an impact on the demand for social services [ 36 , 37 , 38 , 39 ]. Therefore, we analyzed demographic and economic data divided geographically by CSS coverage area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation